Ian's walk : a story about autism - Lears, Laurie; Ritz, Karen (Morton Grove, IL : Albert Whitman, 1998)
A young girl realizes how much she cares for her autistic brother Ian when he gets lost at the park. When her autistic little brother, Ian, wanders off while on a walk to the park, Julie must try to see the world through his eyes in order to find him.
Keywords: Autism -- Fiction; Senses and sensation -- Fiction; Brothers and sisters -- Fiction; Autism -- Fiction; Senses and sensation -- Fiction